Intestinal Calcium Uptake, Shell Quality and Reproductive Hormones Levels of Three Laying Hen Varieties after Prolonged Egg Production - Franco-Jimenez, D.J.; Beck, M.M. (International Journal of Poultry Science, 2005)
Hy-Line W98, W36, and Brown hens are among the most popular strains for commercial egg production. It is of interest to evaluate the differences in performance of old hens of each variety. As part of a larger study, hens of the three varieties were maintained under production longer than 100 weeks of age and hens of each strain were randomly selected for in vitro calcium uptake (CaT) by duodenal cells. Blood samples were collected 4-6 hours prior to oviposition via brachial vein cannulation for plasma estrogen (E2), Luteinizing hormone (LH), and progesterone (P4) determination. Hens were then euthanatized by cervical dislocation and CaT determined. The data were analyzed as a completely randomized design, using the General Linear Model procedure (SAS, Proc GLM, 2001), with strain as a fixed treatment and hen as the experimental unit nested with strain. For W36 hens, CaT was significantly greater than that found in Brown hens (P=0.05) while for W98 did not differ from W36 and Brown strains. P4, E2 and LH concentrations were not significantly different in the three varieties of laying hens. Based on the higher CaT by duodenal cells, these results suggest a higher efficiency of the W36 hens in calcium regulation during the terminal phase of egg production (more than 100 weeks of age) compared to the Brown and W98 hens. However, when specific gravity and thickness of shells were compared, the W36 appeared to have no advantage over W98 (P=0.460 and 0.684) or Brown (P=0.197 and 0.941) hens, respectively.